EKSISTENSI BUDAYA LOKAL GORONTALO SEBAGAI IDENTITAS SUKU BANGSA DALAM DIMENSI GLOBALISASI DAN MODERNISME - Supriyanto Mohi (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2021)
Culture is an ethnic identity that needs to be maintained and preserved to become a source of wealth for the nation and state. Globalization and modern ideologies are presented to provide another space that can assimilate cultural values ​​in each ethnic group, which is commonly referred to as local wisdom. This study aims to explore, study, and obtain descriptive information about Gorontalo local culture as ethnic identity in globalization and modernism dimension. The research method used is qualitative with a phenomenological approach. Data collection techniques were observation, interviews, literature studies, and documentation. The study's findings showed that the existence of the local culture of the Gorontalo people in the use of regional languages ​​and Huyula culture, in general, has experienced quite a tremendous shift in values ​​due to people's misinterpretation of current development through which globalization and modern ideology assimilated. Likewise, the transformation of cultural values ​​through the role of formal, non-formal and informal education and other stakeholders was quite weak.